La friche PCUK entre dépollution, renaturation et régénération paysagère - Elisa Baldin (Projets de Paysage)
The Franco-Belgian industrial basin, between the regions of Wallonia and Hauts de France, is a field of study for mutations in post-industrial landscapes. The research, which is part of a multidisciplinary approach to the study of soils, focuses on projects for the requalification of industrial wastelands that include the environmental remediation techniques in the landscape project. Within this framework, the site known as Produits Chimiques Ugine Kuhlmann (PCUK), within the Lille metropolitan area, is studied as an unique testing ground for observing a succession of approaches adopted since 1984 in the rehabilitation of sites and polluted soils. A notable fact is that requalification strategies are confronted with the legacy of industrial production, namely an artificial topography which, depending on the different techniques used, appears partly transfigured, completely erased, or partly preserved. The comparative study of the different interventions provides indicators for creating a new landscape on a former polluted site by restoring the living soil.